Proteomic analysis of the action of the Mycobacterium ulcerans toxin mycolactone: targeting host cells cytoskeleton and collagen - Gama, José B. (2014)
Buruli ulcer (BU) is a neglected tropical disease caused by Mycobacterium ulcerans. The tissue damage characteristic of BU lesions is known to be driven by the secretion of the potent lipidic exotoxin mycolactone. However, the molecular action of mycolactone on host cell biology mediating cytopathogenesis is not fully understood. Here we applied two-dimensional electrophoresis (2-DE) to identify the mechanisms of mycolactone's cellular action in the L929 mouse fibroblast proteome. This revealed 20 changed spots corresponding to 18 proteins which were clustered mainly into cytoskeleton-related proteins (Dync1i2, Cfl1, Crmp2, Actg1, Stmn1) and collagen biosynthesis enzymes (Plod1, Plod3, P4ha1). In line with cytoskeleton conformational disarrangements that are observed by immunofluorescence, we found several regulators and constituents of both actin- and tubulin-cytoskeleton affected upon exposure to the toxin, providing a novel molecular basis for the effect of mycolactone. Consistent with these cytoskeleton-related alterations, accumulation of autophagosomes as well as an increased protein ubiquitination were observed in mycolactone-treated cells. In vivo analyses in a BU mouse model revealed mycolactone-dependent structural changes in collagen upon infection with M. ulcerans, associated with the reduction of dermal collagen content, which is in line with our proteomic finding of mycolactone-induced down-regulation of several collagen biosynthesis enzymes. Our results unveil the mechanisms of mycolactone-induced molecular cytopathogenesis on exposed host cells, with the toxin compromising cell structure and homeostasis by inducing cytoskeleton alterations, as well as disrupting tissue structure, by impairing the extracellular matrix biosynthesis.